Bisphosphonates and osteonecrosis of the jaws a review of current knowledge - Frange, Melanie Ruth Karganilla
Bisphosphonates have recently been found out to be associated with
Keywords: Bisphosphonates; Osteonecrosis; Jaws; Risk management